Mid-Late Devonian assemblages of herbaceous lycophytes from northern Argentina and Bolivia: Age assessment with palynomorphs and invertebrates and paleobiogeographic importance - Di Pasquo, Mercedes (2015)
Implications of a new collection of lycophytes of the genera Haplostigma Seward and Paleostigma Kräusel and Dolianiti from southern Bolivia and northern Argentina are presented. Fragmented herbaceous stems of lycophytes preserved as compressions, impressions and casts come from the Middle and Late Devonian Pescado (Huamampampa), Los Monos and Iquiri formations at Mataral, Yesera, Angosto del Pescado and Balapuca. The interbedded shales and siltstones bearing the lycophytes were also examined for palynology. They yielded mostly terrestrial palynomorphs with Grandispora pseudoreticulata and other Eifelian to Givetian species and fewer microplanktonic species (i.e., acritarchs, prasinophytes, chitinozoans). At Yesera, diagnostic spores and elements of the microplankton suggest a Givetian-Frasnian up to early Famennian age for the Haplostigma beds. Moreover, presence of the same brachiopod taxon in the Haplostigma intervals at Yesera Dique (palynologically barren) and Yesera Centro supports their correlation. This new information supports terrestrial connections between these Bolivian and Argentine areas and other regions of South America in the Eifelian – Givetian Afrosouthamerican Subrealm, which extended up to the early Famennian.